Pengaruh Sumber Daya Alam dan Infrastruktur Terhadap Pertumbuhan Ekonomi di Kawasan Timur Indonesia dengan Pendekatan Dynamic Panel Data - Brian, Meryam Rayna; Akbar, Urmatul Uska (Jurnal Kajian Ekonomi dan Pembangunan, 2025)
This study aims to determine the extent of influence of natural resources and infrastructure on economic growth in Eastern Indonesia, which includes 13 provinces in the period 2016–2023. This study uses secondary data sourced from the Central Statistics Agency (BPS). With economic growth as the dependent variable and natural resources, electricity infrastructure, road infrastructure, education infrastructure as independent variables, and domestic investment as control variables. The method used is a dynamic panel data approach with Generalized Method of Moments (GMM) estimation using Stata14 software. The results of the study show that in the short term, the variables of previous year's economic growth, natural resources, electricity infrastructure, road infrastructure, and domestic investment have a positive and significant effect on economic growth. Conversely, educational infrastructure shows a negative and significant effect on economic growth. In the long term, it shows that the variables of electricity infrastructure, road infrastructure, and domestic investment have a positive and significant effect on economic growth. Conversely, educational infrastructure shows a negative and significant effect and natural resources have a positive and insignificant effect on economic growth in Eastern Indonesia in 2016–2023.